Sufficiency with the Thai way of Life - (Supan Grasasom), Phrakhru Phimonkanlayanatham; Thitapanyo, Phramaha Mit (Dhammathas Academic Journal, 2019)
This article is about research. sufficiency with the Thai way of life sufficiency refers to moderation, reasonableness, and the need for a good immune system. The primary consideration is the conceptual framework. It is a philosophy that points out the way to live and behave in the way it should be. It is based on the traditional way of Thai society. Can be applied at all times to bring the principles and practices of living with self-reliance. Have a fit with their own convention and environment do not persecute themselves, others have reason to think carefully, do not underestimate. Develop self to keep up with changes in both physical, social, environmental and cultural values. Society with the help of each other. All three elements have a systematic relationship. This article is about research. sufficiency with the Thai way of life sufficiency refers to moderation, reasonableness, and the need for a good immune system. The primary consideration is the conceptual framework. It is a philosophy that points out the way to live and behave in the way it should be. It is based on the traditional way of Thai society. Can be applied at all times to bring the principles and practices of living with self-reliance. Have a fit with their own convention and environment do not persecute themselves, others have reason to think carefully, do not underestimate. Develop self to keep up with changes in both physical, social, environmental and cultural values. Society with the help of each other. All three elements have a systematic relationship. The application of sufficiency means that the society must have sufficient knowledge and understanding of sufficiency economy. The need for people to know the economy that is meaningful modesty, rationality and good immunity in the body. Can live in accordance with economic social conditions. There is a way to behave and act on the sufficiency economy to use in daily life.